SAT-585 Autoregulation of Adipose Tissue Development - Feldman, Brian (J Endocr Soc, 2020)
White adipose tissue not only serves as a reservoir for energy storage but also secretes a variety of hormonal signals and modulates systemic metabolism. A substantial amount of adipose tissue develops in early postnatal life, providing unique access to the formation of this important tissue. However, while a number of factors have been identified that can modulate the differentiation of progenitor cells into mature adipocytes in cell autonomous assays, it remains unclear which are connected to physiological extracellular inputs and are most relevant to tissue formation in vivo. We elucidated that mature adipocytes themselves signal to adipose depot-resident progenitor cells to direct depot formation in early postnatal life and gate adipogenesis when the tissue matures. Our studies reveal that, as the adipose depot matures, a previously unrecognized signal is generated in mature adipocytes that converges on progenitor cells to regulate the cytoskeleton and attenuate the rate adipogenesis in vivo. This signal toggles the adipose depots from developmental to tissue homeostatic levels of adipogenesis.